Handbook of research on foundations and applications of intelligent business analytics - Sun, Zhaohao; Wu, Zhiyou, 1967- (Advances in business information systems and analytics (ABISA) book series., 2022)
"This book addresses research issues by investigating into foundations, technologies, and applications of intelligent business analytics, offering theoretical foundations, technologies, methodologies, and applications of intelligent business analytics in an integrated way"--